2013
DOI: 10.1107/s1600536813031346
|View full text |Cite
|
Sign up to set email alerts
|

4-Formyl-2-nitrophenyl 2-chlorobenzoate

Abstract: In the title compound, C14H8ClNO5, the benzene rings form a dihedral angle of 19.55 (9)°. The mean plane of the central ester group [r.m.s. deviation = 0.024 Å] forms dihedral angles of 53.28 (13) and 36.93 (16)°, respectively, with the nitro- and chloro-substituted rings. The nitro group forms a dihedral angle of 19.24 (19)° with the benzene ring to which it is attached. In the crystal, mol­ecules are linked by weak C—H⋯O hydrogen bonds, forming C(7) chains, which run along [100].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…In the next step, this is changed to elastic by varying molecular orientation so that more isotropic, interlocked packing is favored . The 1D elastic crystals are next modified to two-dimensional (2D) elastic through further structural changes. Finally, the interaction strengths , in the 2D elastic crystal are changed using known chemical principles so that the isotropy is decreased to the extent that plasticity ensues. However, because the basic structural topology is not changed, there are no slip planes in these 2D plastic bendable crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the next step, this is changed to elastic by varying molecular orientation so that more isotropic, interlocked packing is favored . The 1D elastic crystals are next modified to two-dimensional (2D) elastic through further structural changes. Finally, the interaction strengths , in the 2D elastic crystal are changed using known chemical principles so that the isotropy is decreased to the extent that plasticity ensues. However, because the basic structural topology is not changed, there are no slip planes in these 2D plastic bendable crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Access to more than one major bendable direction (here, two) requires nearly mutual perpendicular orientations of the molecules (Figure ), in other words, a herringbone arrangement (Figure b). The literature shows that orthogonal C–H···O interactions are potential contacts to maintain such an arrangement. Compound E3 however is seen to display only 1D elasticity, and there are no side-to-end orthogonal C–H···O interactions (see Figure S15). Then, we used the NO 2 derivative and prepared 4-iodophenyl 4-nitrobenzoate ( 3a ) and 4-iodophenyl 3-methyl-4-nitrobenzoate ( 3b ) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…(Moreno- Fuquen et al, 2013a), 4-formyl-2-nitrophenyl 4-cloro benzoate (F4ClB)(Moreno-Fuquen et al, 2013b) and 4-formyl-2nitrophenyl 3-nitro-2-methyl benzoate (F3N2MB)(Moreno-Fuquen et al, 2014) reported earlier jobs. The benzene rings of (I) form a dihedral angle of 46.36 (8)°.…”
mentioning
confidence: 99%